Strategi Persaingan Industri Dan Peran Kekuatan Pasar Terhadap Pertumbuhan Ekonomi - Nur Hidayatillah; Muhammad Yasin (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Indonesia's economic growth is running quite well as the predictions from the World Bank which estimates an increase in the Indonesian economy of 5.1% in 2016 and 5.3% in 2017, the figure is an improvement from 4.8% in 2015 (The World Bank). Projections made by the World Bank have differences from the Indonesian government's target, according to Finance Minister Bambang Brodjonegoro, the government will keep economic growth at 5.3%.